Contextual Complexities in Implementing a Family-Based Childhood Obesity Intervention: The Perspectives of Enrolled Children and Their Parents - Didde Hoeeg; Ulla Christensen; Louise Lundby-Christensen; Dan Grabowski (MDPI AG, 2020)
Family interventions to treat childhood obesity are widely used, but knowledge about how family dynamics are affected by these interventions is lacking. The present study aims to understand how a family intervention impacts the context of family dynamics, and how different contexts affect the families' implementation of the intervention. Based on qualitative interviews, we studied families with a child between 9-12 years enrolled in a family intervention to treat childhood obesity at a pediatric outpatient clinic. We conducted 15 family interviews including 36 family members. We found that the family intervention created a new context for the enrolled children. They had to navigate in different contexts and non-supportive environments and push for change if they needed more supportive environments in their attempt to adhere to healthy habits. We show the complexities experienced by parents and grandparents when trying to comply with siblings' and/or grandchildren's different needs. The enrolled children were often indirectly blamed if others had to refrain from unhealthy preferences to create supportive environments. These findings are significant in understanding the important role of contexts in family-obesity interventions. This knowledge is relevant to health professionals, researchers, and policymakers.